Unthinkable: Ethico-political Fiction in the Present - Blagojević, Jelisaveta (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Jelisaveta Blagojević Title (English): Unthinkable: Ethico-political Fiction in the Present Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 29-33 Page Count: 5 Citation (English): Jelisaveta Blagojević, “Unthinkable: Ethico-political Fiction in the Present,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011): 29-33.